Being Constrained and Enabled: A Study of Pre-Registration Nursing Students Ethical Practice - Johns, Susan (Auckland University of Technology, 2004)
This study uncovers the experience of being ethical from the perspective of pre-registration nursing students. Using the qualitative methodology of phenomenology, specifically that outlined by van Manen, it seeks to show how students act ethically within everyday practice.Ethics is vital to any health related profession and the growing complexity of New Zealand's health care system requires more responsibility for ethical decision making in nursing care. Providing nursing care is an ethically charged undertaking and despite ethics taking an increasingly important place in nursing education few studies show the contextual nature of ethical practice from the perspective of students. This study aims to partly redress this situation.In this study I have interpreted the experiences of twelve pre-registration students. Using seventeen stories shared by the student participants, my personal understandings and literature, the meaning of being ethical has been illuminated. Three themes emerged from the interpretation. These include 'keeping things 'nice'', 'being true to yourself' and 'being present'. This thesis asserts that the overarching theme within these themes is that of 'being constrained and enabled'. Being constrained shows the experiences of students as they live through the tensions of being and doing as they strive to be ethical. Being enabled shows the experience of self-determination. Finally the study maintains that the shaping of ethical practice for undergraduate students may be enhanced when their reality is positioned and valued within educational processes.
Keywords: Nursing students; Nursing ethic; Health Studies